Mitochondrial Depolarization Is Not Required for Neuronal Apoptosis - Krohn, Aaron J. (J Neurosci, 1999)
Mitochondria are sites of cellular energy production but may also influence life and death decisions by initiating or inhibiting cell death. Mitochondrial depolarization and the subsequent release of pro-apoptotic factors have been suggested to be required for the activation of a cell death program in some forms of neuronal apoptosis. We induced apoptosis in cultured rat hippocampal neurons by exposure to the protein kinase inhibitor staurosporine (STS) (300 nm). The time course of mitochondrial membrane potential (ΔΨ(m)) during apoptosis was examined using the probe tetramethylrhodamine ethyl ester (TMRE). Cells exhibited no decrease in TMRE fluorescence, indicative of mitochondrial depolarization, up to 8 hr after STS exposure. Rather, baseline TMRE fluorescence remained unchanged up to 2 hr and thereafter actually increased significantly. Throughout this time period, the mitochondria could also be depolarized with the protonophore carbonyl cyanidep-trifluoromethoxy-phenylhydrazone (FCCP, 0.1 μm), exhibiting the same relative magnitude of fluorescence release (unquenching) as controls. Even after 16 hr of staurosporine treatment, neurons that showed signs of nuclear apoptosis maintained ΔΨ(m) and could be depolarized with FCCP. In contrast, caspase-3-like activity had increased roughly sevenfold by 2 hr and >20-fold by 8 hr. Double-labeling of hippocampal neurons with the potential-sensitive probe Mitotracker Red Chloromethyl X-Rosamine and an antibody to cytochrome c demonstrated at the subcellular level that mitochondrial cytochrome c release also occurred in the absence of mitochondrial depolarization. These data suggest that mitochondrial depolarization is not a decisive event in neuronal apoptosis.